Longitudinal development of physiological characteristics in elite young males. Issue 2 (20th January 2011) - Hemmings, Steph; Nevill, Mary; Morris, John; Barrett, Laura
Abstract : Background: Cross-sectional studies examining training effects on development of performance variables have been confounded by growth and development changes. In order to examine the relative contribution of training, there was a need to collect 'growth' data longitudinally. Aims and objectives: The purpose of this study was to examine age- and maturity-associated variation in longitudinal physiological characteristics development in elite and non-elite adolescent males. Methods: Longitudinal measures of peak VO2, submaximal VO2, and power output in 11 elite, (13.7–17.8 years), and five non-elite males (13.1–17.6 years), over 2 or 3 consecutive years were examined. Maturity was assessed using Tanner's (1962) indices of secondary sexual characteristics. Results: Sum of skinfolds remained the same in the elite group yet increased in the non-elite. Peak VO2 was greater in the elite males by 9.1 ml/kg/min, with no change in age. Oxygen uptake at 10.6 km/h declined by 1.2 ml/kg/min per year in each group. Percentage peak VO2 at the same running speed was l2% lower in the elite and declined by 1.3% each year in both groups. Blood lactate concentration was 1.5 mmol/l lower in the elite males compared to the non-elite, however there was no decline with age. Peak and mean power output increased disproportionately in the elite group, with percentage fatigue increasing similarly. Conclusion: Body fatness increases across adolescence in the untrained male. Peak VO2 remains stable throughout adolescence but is characteristically higher in elites either as a result of strenuous training or genetic endowment. Running economy improves with age in both elite and non-elite but does not appear to be related to training status. Short-term power output shows a disproportionate increase with age in the elite male athlete compared to the untrained contemporary, which may have been influenced by differences in body composition between groups.